Slavery - De Medeiros, James, 1975- (Black history (Smartbook Media Inc.), 2020)
Traces the history of slavery in America, highlighting notable events and people, and discussing how it changed America and the lives of African Americans. Features photographs, fact boxes, a timeline, an activity, a quiz, and a glossary.